Primary school English teachers' practice of teaching early grade reading - Endrias Yisihak Ukumo; Abebe Damtew Berlie (Social Sciences and Humanities Open, 2024)
The purpose of this study was to investigate Ethiopian public primary school English teachers’ practice of teaching early grade reading. To this end, it used a descriptive research design of mixed methods approach. It attempted to answer basic research questions: a) To what extent are primary school English teachers knowledgeable about teaching early grade reading? b) What does classroom practice of teaching early grade reading look like? Data were collected from thirty (N = 30) English teachers in five randomly selected primary schools through structured classroom observation checklist, 40 multiple choice items knowledge assessment test and semi-structured interview. The data collected through classroom observation checklist and knowledge assessment test were analyzed by Statistical Package for Social Sciences (SPSS version 25.0) to answer basic research questions. The data from semi-structured interview were analyzed in words to substantiate quantitative data. It has been observed that primary school English teachers were not employing appropriate literacy instruction strategies in 60%–80% of lessons observed. English teachers also had knowledge and skill gap about teaching foundational reading skills (Overall mean test score = 43.4 %; 21 (70%) of participant teachers scored <50% while 9 (30%) of teachers scored 50% and above). Out of 40 multiple choice items, 16 (65%) were answered incorrectly while 14 (35%) were answered correctly. More serious knowledge limitations are observable with teaching oral reading fluency, vocabulary and comprehension. Therefore, it is recommended that teacher preparation programs should revisit the emphasis given to teaching early grade reading, and systematic, explicit and hands-on trainings should be given to Ethiopian lower grades English teachers on literacy instruction strategies.